Maternal and Neonatal Circulating Visfatin Concentrations in Patients with Preeclampsia and a Small-For-Gestational Age Neonate - Mazaki-Tovi, Shali (2010)
OBJECTIVE: Maternal circulating visfatin concentrations are higher in patients with a small-for-gestational-age (SGA) neonate than in those who delivered an appropriate-for-gestational age AGA neonate or in those with preeclampsia. It has been proposed that enhanced transfer of visfatin from the fetal to maternal circulation may account for the high concentrations of maternal visfatin observed in patients with an SGA neonate. The aims of this study were: 1) to determine whether cord blood visfatin concentrations differ between normal neonates, SGA neonates and newborns of preeclamptic mothers; and 2) to assess the relationship between maternal and fetal circulating visfatin concentrations in patients with an SGA neonate and those with preeclampsia. STUDY DESIGN: This cross-sectional study included 88 pregnant women and their neonates, as well as 22 preterm neonates in the following groups: 1) 44 normal pregnant women at term and their AGA neonates; 2) 22 normotensive pregnant women and their SGA neonates; 3) 22 women with preeclampsia and their neonates; and 4) 22 preterm neonates delivered following spontaneous preterm labor without funisitis or histologic chorioamnionitis, matched for gestational age with infants of preeclamptic mothers. Maternal plasma and cord blood visfatin concentrations were determined by ELISA. Non-parametric statistics were used for analyses. RESULTS: 1) The median visfatin concentration was lower in umbilical cord blood than in maternal circulation, in normal pregnancy, SGA and preeclampsia groups (p<0.001 for all comparisons); 2) the median cord blood visfatin concentrations did not differ significantly between term AGA or SGA neonates, infants of mothers with preeclampsia and their gestational-age-matched preterm AGA neonates; 3) maternal and cord blood visfatin concentrations correlated only in the normal term group (r= 0.48, p=0.04). CONCLUSION: Circulating visfatin concentrations are lower in the fetal than in the maternal circulation and did not significantly differ between the study groups. Thus, it is unlikely that the fetal circulation is the source of the high maternal visfatin concentrations reported in patients with an SGA neonate.